PENYULUHAN TENTANG PENTINGNYA STUDI EVALUASI LAHAN BAGI MASYARAKAT DI KECAMATAN BATANG TORU - Rahmawaty, Abdul Rauf, T Irmansyah, R. Hamdani Harahap, Simon Tarigan, Nawang Wulan, Christine Pepah (JURNAL BIMA, 2024)
Counseling on land evaluation has an important role for the community in Batang Toru Sub District. Education about the importance of land evaluation studies for the community in Batang Toru Sub District is very important to increase awareness and understanding to increase participation and collaboration, supporting sustainable development. This study aims to educate and increase public awareness regarding the importance of land evaluation in land management and use in Batang Toru Sub District. This activity was carried out in Batang Toru Sub District, South Tapanuli Regency, North Sumatra Province. This outreach is carried out through Focus Group Discussion (FGD) activities and interactive discussions involving various stakeholders, including the community, private companies and local governments. The results of the activity show a change in people's understanding of the importance of plant suitability evaluation studies and efforts to maintain land quality as well as mitigation steps that can be taken to preserve the environment. In addition, this outreach succeeded in encouraging active community participation in the land evaluation and planning process, which in turn strengthened cooperation between communities, government and companies. The results of this activity emphasize the importance of sustainable extension as a tool to achieve better land management to support sustainable development in the Batang Toru area. Thus, this extension contributes to better resource management and environmental protection for community welfare.